Are Changes in (Czech Direct) Tax Law Necessary, or Is It Just a Politicum? - Radvan, Michal (Public Governance, Administration and Finances Law Review, 2022)
This contribution disproves the hypothesis that most of the changes in Czech direct tax law are adopted to minimise negative aspects connected with the Covid-19 pandemic and the Ukrainian war. On the contrary, most of the significant changes in the Czech tax law adopted in the last three years (abolition of the super-gross wage, lump-sum tax, tax relieves, etc.) had no connection to the SARS-CoV-2 coronavirus causing Covid-19 illness or the war in Ukraine. These tragic incidents were just a pretext to advance political goals.